2012
DOI: 10.1073/pnas.1118125109
|View full text |Cite
|
Sign up to set email alerts
|

Maturation cleavage of the murine leukemia virus Env precursor separates the transmembrane subunits to prime it for receptor triggering

Abstract: The Env protein of murine leukemia virus matures by two cleavage events. First, cellular furin separates the receptor binding surface (SU) subunit from the fusion-active transmembrane (TM) subunit and then, in the newly assembled particle, the viral protease removes a 16-residue peptide, the R-peptide from the endodomain of the TM. Both cleavage events are required to prime the Env for receptor-triggered activation. Cryoelectron microscopy (cryo-EM) analyses have shown that the mature Env forms an open cage-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 29 publications
1
42
0
Order By: Relevance
“…Several recent studies have used cryo-electron microscopy (cryo-EM) to examine intermediates in the fusion process mediated by the fusogenic proteins of Moloney murine leukemia virus (32,55), herpes simplex virus 1 (36), influenza virus (15,29), and vesicular stomatitis virus (31). However, no cryo-EM study has yet reported visualization of a prehairpin intermediate.…”
mentioning
confidence: 99%
“…Several recent studies have used cryo-electron microscopy (cryo-EM) to examine intermediates in the fusion process mediated by the fusogenic proteins of Moloney murine leukemia virus (32,55), herpes simplex virus 1 (36), influenza virus (15,29), and vesicular stomatitis virus (31). However, no cryo-EM study has yet reported visualization of a prehairpin intermediate.…”
mentioning
confidence: 99%
“…This suggests that the sequence just proximal to the MSD can modulate functionality. MLV Env is trimeric in the ectodomain and also is modeled to be trimeric in the CTD prior to R-peptide cleavage (11,29). A recent study by Löving et al (29) demonstrated that the membrane-proximal ectodomain of MLV Env is tightly packed prior to R-peptide cleavage.…”
Section: Resultsmentioning
confidence: 99%
“…MLV Env is trimeric in the ectodomain and also is modeled to be trimeric in the CTD prior to R-peptide cleavage (11,29). A recent study by Löving et al (29) demonstrated that the membrane-proximal ectodomain of MLV Env is tightly packed prior to R-peptide cleavage. These pieces of data led us to hypothesize that there are protein contacts in both the glycoprotein ectodomain and CTD that contribute to Env trimerization and that glycoprotein function is inhibited if these two trimer interfaces are not synchronous with each other.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of P148, it is possible that this residue, in combination with glycine at position 147, forms a molecular hinge that allows for a conformational change within the transmembrane domain (p15E/TM) stalk during activation of the fusion mechanism. Recent cryoelectron microscopy imaging data indicate that the CTD of MLV Env holds the ectodomain in a tight conformation; however, cleavage of the R peptide results in a conformational rearrangement in TM wherein the trimer helices are splayed apart, allowing for fusogenic activation of Env (46). The G147-P148 pair at the N terminus of the MSD may facilitate the molecular reordering of TM during this process.…”
Section: Discussionmentioning
confidence: 99%